International Conference on “The Making of the Islamic Diaspora” (American Journal of Islam and Society, 2004)
On 7-9 May 2004, the SSHRC-funded, York University-based MCRI projecton Diaspora, Islam, and Gender project held an international conferenceon “The Making of the Islamic Diaspora.” Under the directorship ofHaideh Moghissi, Saeed Rahnema, and Mark Goodman, the event was heldin Toronto and was cosponsored by the Ford Foundation EducationalProject for Palestinians, the Atkinson Faculty of Liberal and ProfessionalStudies, the York Centre for Refugee Studies, and the York Centre forFeminist Research. The conference brought together an impressive collectionof scholars from around the world to share knowledge and insight intothe challenges that face diaspora communities of emigrants, refugees, andexiles who originate from Islamic cultures, with a specific focus on the genderdimension of displacement.In addition to the invited guests and speakers, the conference wasattended by approximately 50 academics, graduate students, and the publicat large. The conference’s guest of honor was the Honorable Zahira Kamal,Minister of Women’s Affairs for the Palestinian National Authority, whoparticipated in the conference and presented a keynote address at a dinnerreception in her honor.The conference’s panels discussed themes related to identity formation,gender in diaspora, fundamentalism and human rights, the diasporaexperience, and the media and representation. Nergis Canefe, for example,spoke about issues of religious identity and national belonging andnoted that diasporas offer a site of new membership that is different thanmigrants and represent the flourishing of hybrid identities. She describedthe “common immigrant story,” where such socioeconomic barriers asracism, stereotyping, media representation, and difficulty in recertificationmake it extremely difficult to have a smooth life transition in a newcountry ...